PENDAMPINGAN PEMBELAJARAN BAHASA INGGRIS DENGAN MENGGUNAKAN APLIKASI CANVA BAGI SISWA SMK DI KARAWANG - Puspitaloka, Nina; Nurjanah, Kartika Dewi; Ocktavia, Lulu (Universitas Mataram, 2024)
Education plays an important role in creating a superior and competitive young generation. So student creativity needs to be involved to become agents of change in the world of education. Technology is a mainstay for students to be creative, one of which is by creating interesting and effective learning media. One of the vocational schools in Karawang is the main target for English language learning assistance activities on polite request material using the Canva application. The aim of this service is to assist in using the Canva application with various learning materials with visualizations containing English language learning, as well as improving students' creative skills. This service uses observation and interview methods. Apart from that, practice was carried out directly, then questionnaires were distributed to obtain feedback regarding this training, so that the results obtained were very satisfying. Students were able to realize this activity well and create work in the form of posters. This dedication makes students more motivated by making learning interesting and dynamic involving technology, especially in learning English.